2011
DOI: 10.1051/0004-6361/201116662
|View full text |Cite
|
Sign up to set email alerts
|

New Galactic star clusters discovered in the VVV survey

Abstract: Context. VISTA Variables in the Vía Láctea (VVV) is one of the six ESO Public Surveys operating on the new 4-m Visible and Infrared Survey Telescope for Astronomy (VISTA). VVV is scanning the Milky Way bulge and an adjacent section of the disk, where star formation activity is high. One of the principal goals of the VVV Survey is to find new star clusters of different ages. Aims. In order to trace the early epochs of star cluster formation we concentrated our search in the directions to those of known star for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
171
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 109 publications
(173 citation statements)
references
References 44 publications
2
171
0
Order By: Relevance
“…Robitaille et al (2008), Evans et al (2009), andGutermuth et al (2010) used Spitzer data to classify > 13 × 10 3 YSOs. Borissova et al (2011) discovered 96 candidate clusters 2 in the VVV survey (Minniti et al 2010), while Mercer et al (2005) identified 92 star clusters via GLIMPSE data (see also Froebrich et al 2007;Kronberger et al 2006). Those infrared surveys resolved numerous individual cluster stars, and in many instances confirmed existing evidence of star formation put forth by low-resolution surveys (e.g., IRAS and maser observations, Avedisova 2002).…”
Section: Introductionmentioning
confidence: 68%
“…Robitaille et al (2008), Evans et al (2009), andGutermuth et al (2010) used Spitzer data to classify > 13 × 10 3 YSOs. Borissova et al (2011) discovered 96 candidate clusters 2 in the VVV survey (Minniti et al 2010), while Mercer et al (2005) identified 92 star clusters via GLIMPSE data (see also Froebrich et al 2007;Kronberger et al 2006). Those infrared surveys resolved numerous individual cluster stars, and in many instances confirmed existing evidence of star formation put forth by low-resolution surveys (e.g., IRAS and maser observations, Avedisova 2002).…”
Section: Introductionmentioning
confidence: 68%
“…Majaess (2013) has also made a significant contribution on young clusters (see also, Bica et al 2003a,b;Lada & Lada 2003;Mercer et al 2005;Froebrich, Scholz & Raftery 2007;Borissova et al 2011;Solin, Haikala & Ukkonen 2014).…”
Section: Introductionmentioning
confidence: 94%
“…The effort aims to build upon existing catalogs that are complete within only 1 kpc from the Sun (version 3.3 -jan./10/2013 of the Dias et al 2002 catalog; see also Lamers et al 2005;Piskunov et al 2008). In Borissova et al (2011), we presented a catalog of 96 new cluster candidates in the disk area covered by the VVV survey. Most of these clusters were found toward known star forming regions associated with methanol maser emission, hot molecular cores (Longmore et al 2009), Galactic bubbles detected by GLIMPSE (Churchwell et al 2006(Churchwell et al , 2007, and infrared and radio sources.…”
Section: Introductionmentioning
confidence: 99%